2019
DOI: 10.1038/s41467-019-09107-y
|View full text |Cite
|
Sign up to set email alerts
|

Proteome-wide solubility and thermal stability profiling reveals distinct regulatory roles for ATP

Abstract: Adenosine triphosphate (ATP) plays fundamental roles in cellular biochemistry and was recently discovered to function as a biological hydrotrope. Here, we use mass spectrometry to interrogate ATP-mediated regulation of protein thermal stability and protein solubility on a proteome-wide scale. Thermal proteome profiling reveals high affinity interactions of ATP as a substrate and as an allosteric modulator that has widespread influence on protein complexes and their stability. Further, we develop a strategy for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
301
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(318 citation statements)
references
References 63 publications
15
301
0
2
Order By: Relevance
“…Under physiological conditions, proteins involved in phase separated membrane-less nuclear organelles-such as the nucleolus-have been shown to contain an insoluble sub-population [42,43]. We found that aggregators included many such proteins in addition to aggregators that were completely soluble in unstressed conditions ( Fig EV2C).…”
Section: Characterization Of Aggregation-prone Proteinsmentioning
confidence: 73%
See 1 more Smart Citation
“…Under physiological conditions, proteins involved in phase separated membrane-less nuclear organelles-such as the nucleolus-have been shown to contain an insoluble sub-population [42,43]. We found that aggregators included many such proteins in addition to aggregators that were completely soluble in unstressed conditions ( Fig EV2C).…”
Section: Characterization Of Aggregation-prone Proteinsmentioning
confidence: 73%
“…With the 26S proteasome the thermal destabilization was stronger for 19S regulatory particle than for the 20S core particle ( Fig 5F). Interestingly, proteins from the 19S regulatory particle were thermally stabilized when ATP was added to cell lysates [43]. However, the ATP levels were not altered during the heat shock ( Fig EV1: viability measurements based on ATP quantification).…”
Section: Heat Shock-induced Changes In Thermal Stabilitymentioning
confidence: 98%
“…for a series of ligands, which ones interact strongly with protein of interest), rather than rank order comparisons of absolute ligandprotein binding affinity across the proteome. Such biases are an intrinsic feature of chemoproteomic methods and extend even to label-free approaches such as LiP-MS and CETSA, [43][44] whose detection of protein-ligand interactions require ligand binding to alter proteolytic or thermal stability, respectively. Future studies of acyl-CoA/protein interactions will likely benefit from the integration of multiple approaches.…”
Section: Discussionmentioning
confidence: 99%
“…We chose the AKT1 (protein kinase B) as a model system due to its importance in metabolism, proliferation, cell survival, growth and angiogenesis. In AKT1 SIESTA experiment (data in Supplementary Data 6), ATP was used at 500 µM, at which concentration it only acts as a cosubstrate 34 . 31% (123/396) of the proteins annotated in Uniprot as ATP binders were also verified in our experiment.…”
Section: Siesta Identified and Ranked Many Novel Putative Substrates mentioning
confidence: 99%